An update comprehensive review on the effects of transcutaneous electrical nerve stimulation for postnatal physical and psychological disorders - Chen, Beibei; Chen, Chunyan; Zhao, Xiumin; Xu, Yan (Frontiers in Neurology, 2025)
Postnatal rehabilitation is crucial to women’s physical and mental health, not only to the quality of life of the mother herself, but also to the well-being of the whole family. Transcutaneous Electrical Nerve Stimulation (TENS) has been gradually attracting attention as an emerging means of postnatal rehabilitation. We summarized the current evidence related to this topic by a comprehensive review. Relevant studies demonstrated that TENS is effective for treating postnatal rehabilitation. TENS showed a good analgesia without any severe adverse effects with a frequency of 100 Hz with a pulse duration of 100 μs. Pain significantly decreased and comfort increased after having a cesarean delivery in TENS group compared to the control group. TENS can be applied in the treatment of various postnatal disorders, such as musculoskeletal pain, pelvic floor dysfunction (i.e., postoperative urinary retention, fecal incontinence, and pelvic organ prolapse), sexual dysfunction, sleep disorders, and postpartum depression. Postnatal pain, pelvic floor dysfunction, and sexual dysfunction have been found to associated with the promotion of the pro-inflammatory cytokines and the inhibition of immune cell activity. The mechanisms underlying the protective effects of TENS are modulation of inflammatory responses and immune functions. Thus, TENS is a versatile tool in postpartum rehabilitation, addressing physical and psychological sequelae of childbirth. In future, more large-sample multiple RCTs are still warranted to confirm these findings.